43 Evaluation of the Efficacy of L-Isoleucine Supplemented Food and Vitamin D in the Treatment of Acute Diarrhea in Children. (October 2012) - Alam, NH; Ashraf, H
Abstract : Introduction: Antimicrobial peptides represent an important component of the innate defense of organisms and have activities against all microbes. Recently, L-isoleucine and Vitamin D have been found to induce antimicrobial peptides. Therefore, L-isoleucine and vitamin D might have therapeutic potentials in the management of infectious diarrhea. Objectives: The objectives of this study were to examine if addition of L-isoleucine and/or vitamin D to a diet reduces the stool weight and/or duration of acute diarrhea in children. Methods: This was a double blind randomized clinical trial in 107 children aged 6 to 36 months attending the ICDDRB hospital with acute diarrhea: 28 children received: L-isoleucine (2 g/d) added to milk suji; 27 received Vitamin D 1000 IU/d added to Milk suji; 26 L-isoleucine (2g/d) plus vitamin D 1000 IU/d; 26 Milk suji without L-isoleucine and vitamin D. Other managements were similar in all groups. Stool weight(g) and duration of diarrhea were the primary outcomes. Results: There was a trend in stool weight reduction in the groups receiving L-isoleucine and the reduction was significant on day 2 (mean ± SD, L-isoleucine vs. vit D vs. L -isoleucine + vit D vs. control, 276±228 vs. 386±302 vs. 301± 181 vs. 447± 325, p=0.039) and day3 (176±157 vs. 321±273 vs. 276±169 vs. 341±292, p=0.045). The duration of diarrhea was similar in all groups. Conclusion: L-isoleucine supplemented food reduces stool weight in children with acute diarrhea.